DISCOURSE ANALYSIS ON JIWA YANG BERSEDIH SONG LYRICS - Putri Gita Ardiantari, Ida Ayu; Ayu Dian Andriyani, Anak Agung; Swabawa, Ida Bagus Made Satya (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2023)
This research aimed to analyze the message contained in the lyrics of the song “Jiwa Yang Bersedih” by using discourse analysis approach. The primary data in this research are the lyrics of the song entitled “Jiwa Yang Bersedih”. The song lyrics are taken from the sonora.id website. The data were then analyzed using discourse analysis theory which includes language, structure and context of song lyrics. This research used theory by Paltridge (2006) in analyzing discourse elements and Mitchell (2023) in analyzing the lyric structure. Based on the results of the analysis, the song reveals a well-structured composition with a conventional format comprising verses, choruses, an interlude, and an outro. Repetition of specific phrases, especially in the verses and choruses, underlines the empathetic message, emphasizing understanding and support for individuals grappling with sorrow. The narrative flow of the song takes the listener on a journey from an invitation to express emotions to a reaffirmation of strength and the promise of being heard, illustrating resilience in the face of challenges. Linguistic elements, including pronouns, metaphors, imagery, alliteration, and symbolism, are strategically used to establish a personal connection with the listener and vividly convey emotional struggles.